2015
DOI: 10.1176/appi.ps.201400018
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Assessments of the Helpfulness of Treatment for Major Depression: Results From a National Survey

Abstract: About 32% to 47% of adolescents in the general population reported that depression treatment was extremely helpful or helped a lot. This is substantially lower than response rates in clinical trials. The reasons for these divergent findings merit further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Among people who received mental health treatment in the past 12 months, a majority (55-85%) say that they received treatment that was at least somewhat helpful (Alang & McAlpine, 2019;Colman et al, 2014;Edlund et al, 2015;Kuramoto-Crawford et al, 2015;Lippens & Mackenzie, 2011). On a lifetime basis, around two-thirds of people report ever receiving helpful treatment for their disorder (ten Have et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among people who received mental health treatment in the past 12 months, a majority (55-85%) say that they received treatment that was at least somewhat helpful (Alang & McAlpine, 2019;Colman et al, 2014;Edlund et al, 2015;Kuramoto-Crawford et al, 2015;Lippens & Mackenzie, 2011). On a lifetime basis, around two-thirds of people report ever receiving helpful treatment for their disorder (ten Have et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, patientcentered definitions can also help to identify needs that are not fully met by treatment and in turn can inform policy and service responses to address these needs. [6][7][8] Thus, a patient's evaluation of the helpfulness of treatment is an important measure 9,10 that can be collected directly and efficiently 11,12 and, when assessed in population surveys, can help fill a knowledge gap about treatment outcomes at a population level. 11 In epidemiologic studies, approximately 55% to 75% of adults seeking help for depression or other mental health needs say they received treatment or professional contact that was at least somewhat helpful.…”
mentioning
confidence: 99%
“…Wellness strategies, such as listening to music or having adequate sleep, were reported to be helpful and they were associated with perceived treatment effectiveness and greater subjective helpfulness of medication, psychotherapy, and peer support groups (46). In another study on depression among adolescents, counseling and medication were compared in regards to their helpfulness, finding that 32% to 47% of adolescents in the general population perceived depression treatment as extremely or a lot helpful which was lower than the response rate in clinical trials (47). Additionally, adolescents found that medication was more helpful than counseling (47).…”
Section: Introductionmentioning
confidence: 99%
“…In another study on depression among adolescents, counseling and medication were compared in regards to their helpfulness, finding that 32% to 47% of adolescents in the general population perceived depression treatment as extremely or a lot helpful which was lower than the response rate in clinical trials (47). Additionally, adolescents found that medication was more helpful than counseling (47). Regarding treatment adherence, perceived helpfulness may have a role.…”
Section: Introductionmentioning
confidence: 99%